2017
DOI: 10.1021/acs.jafc.6b04982
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of β-Galactosidases from Lactobacillus on Chitin Using a Chitin-Binding Domain

Abstract: Two β-galactosidases from Lactobacillus, including a heterodimeric LacLM type enzyme from Lactobacillus reuteri L103 and a homodimeric LacZ type β-galactosidase from Lactobacillus bulgaricus DSM 20081, were studied for immobilization on chitin using a carbohydrate-binding domain (chitin-binding domain, ChBD) from a chitinolytic enzyme. Three recombinant enzymes, namely, LacLM-ChBD, ChBD-LacLM, and LacZ-ChBD, were constructed and successfully expressed in Lactobacillus plantarum WCFS1. Depending on the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
3
15
1
Order By: Relevance
“…However, the V max (14.57 nmol/min/µg) and K cat (0.07 min −1 ) of I-ChBD-CadA were lower than that of ChBD-CadA, which indicated that the activity of ChBD-CadA decreased after immobilization. Pham et al (2017) also found the activity of β-galactosidases declined after immobilization on chitin, which was similar with our study.…”
Section: The Effect Of Chbd On 3d Structure Of Cadasupporting
confidence: 92%
See 4 more Smart Citations
“…However, the V max (14.57 nmol/min/µg) and K cat (0.07 min −1 ) of I-ChBD-CadA were lower than that of ChBD-CadA, which indicated that the activity of ChBD-CadA decreased after immobilization. Pham et al (2017) also found the activity of β-galactosidases declined after immobilization on chitin, which was similar with our study.…”
Section: The Effect Of Chbd On 3d Structure Of Cadasupporting
confidence: 92%
“…These results suggested that the fusion of ChBD affected the expression of CadA gene. Other studies also reported that the gene expression will decline after fusion of ChBD or other genes (Pham et al, 2017), which are similar with this study.…”
Section: Construction and Expression Of Fusion Genesupporting
confidence: 91%
See 3 more Smart Citations